2023
DOI: 10.3389/fpubh.2023.1148105
|View full text |Cite
|
Sign up to set email alerts
|

Psychological workplace violence and its influence on professional commitment among nursing interns in China: A multicenter cross-sectional study

Abstract: BackgroundPsychological workplace violence (WPV) is the primary form of workplace violence suffered by nursing interns. Psychological WPV not only damages the physical and mental health of nursing interns, but also has a negative impact on their work quality and career choice.AimTo investigate the characteristics and types of psychological WPV suffered by nursing interns in China, analyze the influencing factors of psychological WPV among nursing interns, and explore the influence of psychological WPV on the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Nursing students attribute the vertical violence they experience during clinical work primarily to a lack of information and guidance [74], while, on the contrary, students exposed to intense clinical stress but with high social support from teachers obtain optimal results [75]. Verbal and psychological violence also has serious effects on nursing students who complain about high job strain, low social support, and low organizational justice [76] that produce a negative effect on their professional commitment [77]. Workplace violence in HCWs may be associated with burnout and the intention to quit [78], although this relationship can be mediated by work ability [79].…”
Section: Discussionmentioning
confidence: 99%
“…Nursing students attribute the vertical violence they experience during clinical work primarily to a lack of information and guidance [74], while, on the contrary, students exposed to intense clinical stress but with high social support from teachers obtain optimal results [75]. Verbal and psychological violence also has serious effects on nursing students who complain about high job strain, low social support, and low organizational justice [76] that produce a negative effect on their professional commitment [77]. Workplace violence in HCWs may be associated with burnout and the intention to quit [78], although this relationship can be mediated by work ability [79].…”
Section: Discussionmentioning
confidence: 99%
“…A review of 132 research papers on musculoskeletal diseases related to nursing work indicated that the annual average prevalence of low back pain among nurses is 55% [1]. Low back pain often leads to restricted work and life activities or disability, posing a threat to the productivity and stability of the registered nurse workforce [2-4].…”
Section: Introductionmentioning
confidence: 99%